Insecticidal effects of dsRNA targeting the Diap1 gene in dipteran pests. Issue 1 (December 2017) - Powell, Michelle; Pyati, Prashant; Cao, Min; Bell, Howard; Gatehouse, John; Fitches, Elaine
Abstract TheDrosophila melanogaster (fruit fly) geneDiap1 encodes a protein referred to as DIAP1 (D rosophila I nhibitor ofA poptosisP rotein 1) that acts to supress apoptosis in "normal" cells in the fly. In this study we investigate the use of RNA interference (RNAi) to control two dipteran pests, Musca domestica andDelia radicum, by disrupting the control of apoptosis. Larval injections of 125–500 ng ofDiap1 dsRNA resulted in dose-dependent mortality which was shown to be attributable to down-regulation of target mRNA. Insects injected withDiap1 dsRNA have approx. 1.5-2-fold higher levels of caspase activity than controls 24 hours post injection, providing biochemical evidence that inhibition of apoptotic activity by theDiap1 gene product has been decreased. By contrast adults were insensitive to injected dsRNA. Oral delivery failed to induce RNAi effects and we suggest this is attributable to degradation of ingested dsRNA by intra and extracellular RNAses. Non-target effects were demonstrated via mortality and down-regulation ofDiap1 mRNA levels inM. domestica larvae injected withD. radicum Diap1 dsRNA, despite the absence of 21 bp identical sequence regions in the dsRNA. Here we show that identical 15 bp regions in dsRNA are sufficient to trigger non-target RNAi effects.